Cytosolic galectin-3 and -8 regulate antibacterial autophagy through differential recognition of host glycans on damaged phagosomes. (23rd February 2018) - Weng, I-Chun; Chen, Hung-Lin; Lo, Tzu-Han; Lin, Wei-Han; Chen, Huan-Yuan; Hsu, Daniel K; Liu, Fu-Tong
Abstract: While glycans are generally displayed on the cell surface or confined within the lumen of organelles, they can become exposed to the cytosolic milieu upon disruption of organelle membrane by various stresses or pathogens. Galectins are a family of β-galactoside-binding animal lectins synthesized and predominantly localized in the cytosol. Recent research indicates that some galectins may act as "danger signal sensors" by detecting unusual exposure of glycans to the cytosol. Galectin-8 was shown to promote antibacterial autophagy by recognizing host glycans on ruptured vacuolar membranes and interacting with the autophagy adaptor protein NDP52. Galectin-3 also accumulates at damaged phagosomes containing bacteria; however, its functional consequence remains obscure. By studying mouse macrophages infected with Listeria monocytogenes (LM), we showed that endogenous galectin-3 protects intracellular LM by suppressing the autophagic response through a host N -glycan-dependent mechanism. Knock out of the galectin-3 gene resulted in enhanced LC3 recruitment to LM and decreased bacterial replication, a phenotype recapitulated when Galectin-8-deficient macrophages were depleted of N -glycans. Moreover, we explored the concept that alterations in cell surface glycosylation by extracellular factors can be deciphered by cytosolic galectins during the process of phagocytosis/endocytosis, followed by rupture of phagosomal/endosomal membrane. Notably, treatment of cells with sialidase, which removes sialic acid from glycans, resulted in increased galectin-3 accumulation and decreased galectin-8 recruitment at damaged phagosomes, and led to a stronger anti-autophagic response. Our findings demonstrate that cytosolic galectins may sense changes in glycosylation at the cell surface and modulate cellular response through differential recognition of glycans on ruptured phagosomal membranes.